Maze of deception - Hand, Elizabeth (Star wars, Boba Fett, 2003)
Young Boba Fett forms an uneasy alliance with rival bounty hunter Aurra Sing in an attempt to find the fortune Boba's late father has hidden on the planet of Aargau.